The role of non-synchronous trading in G7 financial markets - D. Dimitriou; Kenourgios, D.; Simos Th.; A. Tsioutsios (International Journal of Finance & Economics, 2025)
We investigate the effects of non-synchronous trading on volatility spillover for the G-7 equity markets during the Eurozone sovereign debt crisis (ESDC) and the Covid-19 pandemic crisis. For data synchronisation we utilise ΜΑ(1) adjusted return series to estimate the Baba-Engle-Kraft-Kroner (BEKK) and the dynamic conditional correlation (DCC) models. We also consider the use of realised kernels as explanatory variables in the variance equation. In this set up, the contagion effects during crises periods are more perceptible, as the spikes are easier to interpret. We also check the robustness of our main results by applying, wavelet coherence analysis to G-7 major equity indices with realised kernels, as well as local Gaussian correlations (LGC). Our findings suggest the empirical significance of the synchronisation effects for the US and the other G-7 equity markets. We also conclude that realised kernels is an effective tool for mitigating non-synchronous effects. These results underline the significance of quantifying the synchronisation effects in equity markets as well as international portfolio diversification strategies.